Wear characteristics of Al-Si alloys - Torabian H.; Pathak J.P.; Tiwari S.N. (My University, 2025)
The wear characteristics of Al-Si alloys containing 2-20 wt.% have been studied using a pin-on-disc type wear testing machine at room temperature. The effects of alloy composition, sliding distance, sliding speed and load on wear rate of Al-Si alloys have been investigated. It has been found that the wear rate is strongly dependent on alloy composition, applied load and sliding speed. The wear rate decreases and the load-bearing capacity of the alloy increases with increasing silicon content. The nature of the wear process changes with alloy composition and experimental conditions. © 1994.